In vivo Evaluation of Acoustoelastography in the Normal Equine Superficial Digital Flexor Tendon. (9th September 2013) - Brounts, S.H.; Ellison, M.E.; Duenwald‐Kuehl, S.; Forrest, L.; Vanderby Jr, R.
Abstract : Introduction: Superficial digital flexor tendon (SDFT) injury is common in athletic horses. Recovery requires balancing rest and controlled exercise, resulting in high risk of re‐injury. It is difficult to determine the level of work the damaged tissue can sustain based on serial ultrasound examination alone. However, as small changes in sonographic appearance are associated with large changes in biomechanical strength, it is difficult to determine the degree of activity the tissue can sustain. Aims: Acoustoelastography (AEG) is a new ultrasound‐based model to evaluate tendon function. Acoustoelastography deduces stiffness gradient, the rate of change of normalised stiffness as a function of strain, by analysing the changes in echo intensity observed in cine loops captured from gradually deforming tendon. The goal of this project was to establish a reproducible method for applying AEG in the normal equine SDFT. Methods: Fifteen horses with no history of lameness and normal lameness examinations were recruited with informed owner consent and in accordance with the University Research Animal Resources Center. Stiffness gradient index (SGI) and dispersion values (DV) for the palmar SDFT were evaluated at 3 sites (5, 10 and 15 cm distal to the accessory carpal bone [DACB]) by 2 observers. Lifting of the contralateral forelimb during image acquisition resulted in the required SDFT deformation. Interobserver repeatability, intraobserver repeatability, and right‐to‐left limb symmetry were evaluated. Results: The SGIs and DVs for the SDFT at different locations, as well as effects of age or gender, showed no statistical difference (P>0.05). Interclass correlations evaluating repeatability within the same observer, between observers, and symmetry between right and left limbs demonstrated excellent agreement. Conclusions and practical significance: This study shows that AEG is a feasible and repeatable technique for measuring stiffness gradients in normal equine SDFTs. This study will provide the basis for developing a simple, noninvasive evaluation of tendon function that could vastly improve the ability to detect, monitor and treat tendon injuries. Ethical animal research: All animal protocols were approved by the University of Wisconsin Research Animal Resources Center. Client‐owned horses were used for the study and informed consent was obtained.Sources of funding: Research supported by Companion Animal Grant through University of Wisconsin.Competing interests: Co‐author/collaborator Ray Vanderby has patent on acoustoelastography post processing ultrasound‐based tissue evaluation technique.